2019
DOI: 10.1002/ece3.5164
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐ And tissue‐specific differences in telomere length in a reptile

Abstract: The usage of telomere length (TL) in blood as a proxy for the TL of other tissues relies on the assumption that telomere dynamics across all tissues are similar. However, telomere attrition can be caused by reactive oxygen species (ROS) which may vary with metabolic rate, which itself varies across organs depending upon the life history strategy of an organism. Thus, we chose to measure the telomeres of various cell types in juvenile painted dragon lizards, Ctenophorus pictus, given their unusual life history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
1
33
2
Order By: Relevance
“…However, we have a poor understanding of the relationship between blood cell telomere dynamics and the telomere dynamics of other tissue types for most taxa. In the current study, we found a positive correlation between sperm and blood telomeres, but lifehistory traits interact with the telomeres of these cell types differently (Rollings et al 2019). It is possible that the correlation we have observed may be strengthened by interstitial telomeres, which qPCR cannot exclude (Foote, Vleck, & Vleck, 2013.…”
Section: Discussioncontrasting
confidence: 53%
“…However, we have a poor understanding of the relationship between blood cell telomere dynamics and the telomere dynamics of other tissue types for most taxa. In the current study, we found a positive correlation between sperm and blood telomeres, but lifehistory traits interact with the telomeres of these cell types differently (Rollings et al 2019). It is possible that the correlation we have observed may be strengthened by interstitial telomeres, which qPCR cannot exclude (Foote, Vleck, & Vleck, 2013.…”
Section: Discussioncontrasting
confidence: 53%
“…Although telomere lengths seem to correlate among tissues (e.g. in reptiles: Rollings et al., 2019, 2020), differences in cell division and turnover rate, together with the possible tissue‐specific expression of buffering mechanisms, may imply divergent responses in ageing‐related mechanisms at the tissue level. Evidence from mammals suggests that telomere attrition rates are similar across tissues in adults, but not necessarily so in early life (Daniali et al, 2013; Sabharwal et al., 2018), so the life stage at which the temperature effects occur could be important.…”
Section: Candidate Mechanisms To Buffer the Effects Of Warming On Agementioning
confidence: 99%
“…Previous studies in mammals have shown correlation in telomere length among DNA samples from blood cells and different tissues (Okuda et al 2002, Takubo et al 2002, Benetos et al 2011, Daniali et al 2013, Laubenthal et al 2016. In non-model vertebrates, one study in zebra finch Taeniopygia guttata and one in painted dragon Ctenophorus pictus showed that telomere length from blood cells significantly correlates with telomere length in some tissues, but not all (Reichert et al 2013, Rollings et al 2019, but see Parolini et al 2019 for lack of relationship between different somatic tissues excluding blood). Noteworthy, it has also been suggested that the correlation in telomere length between tissues might depend on the life-stage at sampling (Schmidt et al 2016), with a weakening correlation between tissues with increasing age.…”
Section: Introductionmentioning
confidence: 98%